Phase I trial on the safety of olprinone for low central venous pressure management aimed at haemorrhage control during open and laparoscopic hepatectomy: a study protocol - Katsuhiko Uesaka; Yuya Miura; Teiichi Sugiura; Ryo Ashida; Katsuhisa Ohgi; Mihoko Yamada; Shimpei Otsuka; Yoshiyasu Kato; Takuya Oyakawa; Eiji Ando; Sunao Tamai (BMJ Open)
Introduction Hepatectomy is the primary treatment for malignant liver tumours. It is crucial to control bleeding during liver parenchymal transection. Methods to reduce central venous pressure (CVP), such as fluid restriction and the use of vasodilators, are essential for minimising bleeding but can lead to haemodynamic instability. Phosphodiesterase-3 (PDEIII) inhibitors such as milrinone have shown efficacy in managing low CVP and maintaining haemodynamic stability. This study investigates olprinone, another PDEIII inhibitor with a potentially strong vasodilatory effect, for its safety and efficacy in CVP management during hepatectomy.Methods and analysis This single-centre phase I trial at Shizuoka Cancer Center evaluates the intraoperative administration of olprinone for open and laparoscopic hepatectomy. The trial employs a 3+3 cohort study design to determine the maximum tolerated dose (MTD) and identify dose-limiting toxicities. The study also assesses the trends in CVP and circulatory dynamics using the FloTrac System, alongside safety evaluations. The trial aims to establish the safety and MTD of olprinone during hepatectomy, potentially offering a method to control CVP without causing haemodynamic instability. This could lead to reduced blood loss, shorter operative time and fewer postoperative complications.Ethics and dissemination The study protocol was approved by the Certified Review Board of Shizuoka Cancer Center (approval number CRB4180010).Trial registration number jRCTs041230110 and jRCTs041230111.